Spoken English language errors among Jordanian secondary students - Mashoor, Bakheet Bayan Nayif
English language is now deemed as one of the most important languages in the world that has been widely used in many aspects of life such as education, economy, politics, etc. where its usage is equally important both in written and spoken forms. Although the English language has become the world's main language for communication, many EFL students in Jordan have troubles in speaking the English language. In light of speaking skills, most of them fail to communicate well. Students commit errors in various aspects of language including phonetics, morphology, semantics and grammar. This study aims to investigate the structural errors that occur in spoken English language among Jordanian secondary school students. This study involved thirty-one students, four English teachers and one officer from the Ministry of Education in Jordan. The data were obtained from semi-structured interviews. The researcher adopted thematic analysis to analyse the interview in order to shed light on some issues related to the causes of errors made by the students on spoken English language. Subsequently, the interview data were transcribed and analysed by using the Error analysis procedures with the Surface Strategy Taxonomy as the main theory consisting of four categories, they are errors of omission, addition, misinformation and misordering. Besides, the analysis of errors was also made from the syntactical aspects. The study revealed that most students committed four categories of errors in their spoken English language according to the Surface Strategy Taxonomy, namely errors of omission, errors of addition, errors of misinformation and errors of misordering. It was also revealed that the highest errors involved errors on omission and addition, and errors were also found in the use of auxiliary verbs, articles, subject-verb agreements, etc. It was also shown from the research that the causes of errors in their spoken English language were not merely due to the influence of their mother tongue, but also sourced from the curriculum, teachers and students themselves. Some other factors that impeded their excellence and progress in spoken language were related to the number of school hours, teaching methods, equipment and lack of language environment to stimulate language learning. Motivation and lack of practice were also identified as the stumbling blocks in improving their ability to speak the English language well. The study has managed to shed light on some issues related to the causes of errors in spoken English language among secondary school students in Jordan by getting some feedback from the teachers, officer of education ministry and from the students themselves. The study has some implications on the pedagogical and practical aspects of teaching and learning of the English language. It is necessary for students to take part in classroom speaking activities and to be involved in group work. Motivation is much needed because students need to be encouraged to express themselves, their ideas, to ask questions and communicate with the others.